The Uniqueness of Mediation as an Alternative Dispute Resolution Method Outside the Court in Resolving Various Customary Disputes in Simalungun Regency - Abdul Rahman Maulana Siregar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Mediation as an alternative dispute resolution outside the court has its own uniqueness in resolving various customary disputes. Generally, when a dispute arises between parties, the community tends to be more familiar with resolving disputes through customary means, or what they refer to as mediation. Mediation is a term commonly used by the community when disputes occur. Thus, mediation as an alternative dispute resolution holds a unique position among the people, particularly in Simalungun Regency, in resolving various customary disputes without the involvement of the courts. This article will further discuss the uniqueness of mediation in resolving customary disputes, the advantages and disadvantages of applying mediation as an alternative dispute resolution outside the court in Simalungun Regency. The importance of establishing mediation as an effective method for alternative dispute resolution outside the court for various customary disputes lies in its easy procedures, active involvement of the disputing parties, and respect for customary values and norms in maintaining social harmony and prioritizing win-win solutions. Moreover, mediation not only provides a practical and efficient solution but also helps to strengthen social relationships and preserve local cultural continuity. Therefore, mediation is considered a suitable and beneficial means for resolving customary disputes, offering a more familial approach compared to court resolution processes.